PRAKTIK AKUNTABILITAS DALAM PROGRAM KERELAWANAN MILENIAL - Kamila, Aisyah; Wijayanti, Anita (Faculty of Economics and Business University of Mataram, 2023)
This study aims to understand the accountability practice of a milenial volunteering program in Indonesia. Data collection was carried out, among others, through interviews with various stakeholders throughout April 2023, documentation, and participatory observation through a retrospective approach when researchers were involved in the program. Data analysis was carried out by reduction, grouping, and triangulation, which were intended to ensure the research results were unbiased. The findings of this study state that Bakti Millennial considers accountability as a process of maintaining the trust and meeting the expectations of all stakeholders involved. Accountability practices in a formal form include project documents, performance evaluation and achievement, and reports on the use of funds. Furthermore, accountability practices in informal forms are also carried out by implementing communication strategies that involve various parties and documentation through social media, both of which have created an inclusive accountability structure. Forms of accountability are seen in activities such as community service, communication with stakeholders, program preparation, and reporting through the media. This program demonstrates accountability to internal and external stakeholders, intending to meet their expectations and demands and build trust in the organization. By implementing accountability that meets stakeholder expectations, Bakti Millennial can strengthen the foundation of trust and maintain organizational sustainability.